Calibration And Measurement Of Radar Cross-Sections Of Natural And Synthetic Targets - Lo , Yew Chiong (2005)
A polarimetric radar cross section (RCS) calibration technique using two electrically large reference reflectors is developed and experimentally verified. The antennas and the two orthogonal channels in the radar system are modeled as a two -port network.